2007
DOI: 10.1590/s0100-879x2007001100004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between lactose absorption and the C/T-13910 and G/A-22018 mutations of the lactase-phlorizin hydrolase (LCT) gene in adult-type hypolactasia

Abstract: The C/T-13910 mutation is the major factor responsible for the persistence of the lactase-phlorizin hydrolase (LCT ) gene expression. Mutation G/A-22018 appears to be only in co-segregation with C/T-13910. The objective of the present study was to assess the presence of these two mutations in Brazilian individuals with and without lactose malabsorption diagnosed by the hydrogen breath test (HBT). Ten milk-tolerant and 10 milk-intolerant individuals underwent the HBT after oral ingestion of 50 g lactose (equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 22 publications
(30 reference statements)
4
41
0
3
Order By: Relevance
“…This is not the case for African Caribbean Colombians, because the blacks brought as slaves from Africa during the colonial period came mainly from Western Africa where the -13910*T allele is scarce (18,29) . The importance of the ethnic origin, when doing genotype-phenotype correlation studies is evident with the results recently published in Brazil by Bulhões et al (3) and Mattar et al (15) who reported perfect correlation between the SNP C/T -13910 and lactose digestion. They got this result because the subjects in their study were Brazilians of Caucasian descendence.…”
Section: Discussionmentioning
confidence: 69%
“…This is not the case for African Caribbean Colombians, because the blacks brought as slaves from Africa during the colonial period came mainly from Western Africa where the -13910*T allele is scarce (18,29) . The importance of the ethnic origin, when doing genotype-phenotype correlation studies is evident with the results recently published in Brazil by Bulhões et al (3) and Mattar et al (15) who reported perfect correlation between the SNP C/T -13910 and lactose digestion. They got this result because the subjects in their study were Brazilians of Caucasian descendence.…”
Section: Discussionmentioning
confidence: 69%
“…It is estimated that 75% of adults worldwide show some decrease in lactase activity (hypolactasia), resulting in lactose intolerance still during adulthood. The phenomenon "lactose intolerance" is mainly found in African, Asian, South American and South European regions (Bulhões et al, 2007). Unfortunately, this frequently occurring of lactase activity deficiency hampers a broader application of whey for nutrition of mankind.…”
Section: General: the Need For Sustainable Utilization Of Wheymentioning
confidence: 99%
“…Lactose waste increases biochemical and chemical oxygen demand (BOD and COD) which is in contrast with legal standards for wastewater (Cuartas-Uribe et al, 2009). In addition, lactose, as a disaccharide, is scarcely digestible for about 75% of adults worldwide due to lack of β-galactosidase enzyme in their body (Sieber et al, 1997;Bulhões et al, 2007). Furthermore, a high amount of lactose in dairy products like ice cream, condensed milk, etc., leads to an undesirable grainy texture.…”
Section: Introductionmentioning
confidence: 99%